Avaliação de desempenho na gestão estratégica da produção e operações em uma indústria brasileira - Gass, Larissa (2021)
Performance evaluation in the area of production and operations management must be linked to the organization's strategy and must recognize the uniqueness of the decision-making context. Therefore, the objective of the work was to build a performance evaluation model to support the strategic management of production and operations in a large Brazilian industry. The Multicriteria Decison Aid – Constructivist (MCDA-C) was used to build the performance evaluation model. The main results of the survey were: (i) the model built for the performance evaluation of production and operations management is answered by three main areas of concern, being "Product", "Relationship with Customers and Consumers" and "Management of People"; (ii) the built model has 83 evaluation criteria; (iii) the global performance evaluation of the context was 41 points, considered competitive on a scale in which 0 points (neutral level) and 100 points (good level); and, (iv) in order to adopt improvements to the context, action plans were drawn up for descriptors with compromising performance, which raised the global assessment to 70 points. The research brought practical results, providing the organization with a unique model for evaluating the performance of the decision-making context, making it possible to verify the impact of actions on the strategic performance of production and operations management, as well as theoretical results, providing the literature with a performance evaluation model from a constructivist perspective, identified as a lack in the literature review carried out.